Is Bail-in Debt Bail-inable? - Sunjoo Hwang (KDI Journal of Economic Policy, 2019)
The contingent convertible bond (or CoCo) is designed as a bail-in tool, which is written down or converted to equity if the issuing bank is seriously troubled and thus its trigger is activated. The trigger could either be rule-based or discretion-based. I show theoretically that the bail-in is less implementable and that the associated bail-in risk is lower if the trigger is discretion-based, as governments face greater political pressure from the act of letting creditors take losses. The political pressure is greater because governments have the sole authority to activate the trigger and hence can be accused of having 'blood on their hands'. Furthermore, the pressures could be augmented by investors' self-fulfilling expectations with regard to government bailouts. I support this theoretic prediction with empirical evidence showing that the bailin risk premiums on CoCos with discretion-based triggers are on average 1.13 to 2.91%p lower than CoCos with rule-based triggers.
Keywords: G01; G12; G21; G28; 330; Contingent Convertible Bonds; Bail-ins; Discretion-based Triggers; Rule-based Triggers